The Influence of Work Ethic on Public Services: Lessons from a Distant Indonesian Local Public Organization - Leonardus Mangago (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This research aimed to identify and analyze the principles, standards, elements, and quality of public services at the Office of Industry, Trade, and Cooperatives of Yahukimo Regency, Indonesia, located in a remote area. The research method applied was a qualitative descriptive survey with observation and interviews. The interviewees in this study were from 15 informants of different position levels. This study employed an interactive model to analyze the interview data. There were four main findings; firstly, in terms of the principle of public service transparency, the public was increasingly motivated to convey their demands, requests, and aspirations to the government. Meanwhile, accountability services were satisfactory per the provisions of laws and regulations, but public participation in public services was still lacking. Secondly, public service standards and service procedures were implemented following the stipulated provisions and competencies of officials. Those public officers had related-abilities in the form of knowledge, prowess, skill, attitude, and behavior that are required in completing their duties. Thirdly, in terms of public services, the public officers’ work ethic was a driving force for the officials to comply with the prior-set and agreed with rules and work procedures. At the same time, the facilities and infrastructure were adequate. Finally, regarding the quality of public services, the goals and targets of the service were well achieved.